Taxonomic notes on Onosma wardii (Boraginaceae) from Southwestern China - He, Yi; Huang, Ti-Ran; Liu, Dan-Hui; Liu, Quan-Ru (Phytotaxa, 2020)
Critical examination of herbarium specimens and living plants has shown that Onosma mertensioides, O. tenuicaulis, O. zayuensis, O. xiangchengensis are conspecific with O. wardii, so the previous four names are here relegated to the synonymy of the latter.